Protease sensitivity and nuclease resistance of the scrapie agent propagated in vitro in neuroblastoma cells. - Neary, K (1991)
The scrapie agent has been propagated in vitro in mouse neuroblastoma cells. To further characterize the tissue culture-derived scrapie agent, we studied the effects of protease and nuclease digestion on the agent derived from these cells. The scrapie agent in these cells was found to be resistant to protease digestions for short times but was inactivated by prolonged digestion at high protease concentrations. In contrast, digestion with a variety of nucleases did not alter the agent titer. These results demonstrate that the agent requires an essential protein or proteins for infectivity. If the agent also contains a nucleic acid genome, it must be more nuclease resistant than the majority of cellular DNA and RNA. These properties of the tissue culture-derived scrapie agent were identical to those of brain-derived scrapie agent and thus cannot be attributed to secondary effects of tissue pathology, since the infected cell cultures show no cytopathic effects as a result of infection.